Analysis of HIRLAM NWP Model During an Air Pollution Episode in Istanbul in 2009 - Toros, Hüseyin; Geertsema, Gertie; Cats, Gerard; İncecik, Selahattin (Springer Netherlands, 2011)
Meteorological forecasts have been analyzed in detail during an episode involving substantially high concentrations of PM10 that occurred in Istanbul on 18–20 November 2009. The episode addressed here is associated with areas of high pressure over the Northwest of Turkey. These conditions caused poor air quality, especially in the Istanbul Metropolitan Area. Simulations were executed with version 7.2.1 of the HIRLAM model. The simulations were able to predict the temperatures, wind speeds and relative humidity at near surface.